Community-based vision rehabilitation provision in England. (September 2016) - Rabiee, Parvaneh; Bernard, Sylvia; Baxter, Kate; Parker, Gillian
Sight loss is more common among older than younger people. With an ageing population and increasing pressure on health and social care services, preventive and rehabilitation services are being prioritised. However, evidence around community-based vision rehabilitation services is underdeveloped. The focus of this article is on the prevalence, organisational models and capacity of community-based vision rehabilitation services in England that are wholly or partly funded by local authorities (LAs). In all, 89 of the 152 (57%) LAs responded to an online survey about vision rehabilitation services. Services vary widely in the type of provider, type of support offered, structure and skills of the team delivering interventions, caseloads and waiting times. Voluntary organisations appear to experience more pressure on budgets and staffing ratios than LA in-house services. The article discusses implications for practice.